2007
DOI: 10.1161/circulationaha.106.657379
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac Tissue Engineering in an In Vivo Vascularized Chamber

Abstract: Background— Cardiac tissue engineering offers the prospect of a novel treatment for acquired or congenital heart defects. We have created vascularized pieces of beating cardiac muscle in the rat that are as thick as the adult rat right ventricle wall. Method and Results— Neonatal rat cardiomyocytes in Matrigel were implanted with an arteriovenous blood vessel loop into a 0.5-mL patented tissue-engineering chamber… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
146
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 206 publications
(150 citation statements)
references
References 53 publications
(57 reference statements)
4
146
0
Order By: Relevance
“…The inner volume of 16 cm 3 in our chamber in a cylindrical shape emulates a given volume of tissue that certainly would not be sufficiently nourished by diffusion only, thus approaching clinically relevant dimensions. This is the first study demonstrating de novo formation of axially vascularized connective tissue overcoming the previous limitation to tissue volumes below 1 cm 3 (Bach et al, 2006;Lokmic et al, 2007;Morritt et al, 2007).…”
Section: Discussionmentioning
confidence: 86%
“…The inner volume of 16 cm 3 in our chamber in a cylindrical shape emulates a given volume of tissue that certainly would not be sufficiently nourished by diffusion only, thus approaching clinically relevant dimensions. This is the first study demonstrating de novo formation of axially vascularized connective tissue overcoming the previous limitation to tissue volumes below 1 cm 3 (Bach et al, 2006;Lokmic et al, 2007;Morritt et al, 2007).…”
Section: Discussionmentioning
confidence: 86%
“…Following implantation in vivo, vascularization is the mechanism for increasing the thickness of viable and functional tissue. Two representative examples include the implantation of stacked monolayer sheets of CM 36 and the use of a vascularized chamber 37 .…”
Section: Anticipated Resultsmentioning
confidence: 99%
“…In vitro engineered neonatal myocardial sheets of thicknesses up to 200 μm survive, become vascularized and electrically coupled with the host myocardial cells when grafted onto the surface of an infarcted heart [10]. Myocardial tissue could be engineered in larger amount and thickness in vivo using femoral arteriovenous loop enclosed in a subcutaneous chamber [11]. However, direct observation of angiogenesis was not possible in these studies.…”
Section: Discussionmentioning
confidence: 99%
“…The organized atrial tissue contractions had a higher rate than the ventricular one, consistent with the rates observed physiologically in murine hearts. Morritt et al [11] reported that some cardiac tissue constructs that did not spontaneously contract at tissue harvest readily responded when paced. We did not pace these implants externally during the in vivo microscopic observation to preserve the longevity of skin-fold chambers.…”
Section: Discussionmentioning
confidence: 99%